Building Bodies - Moore, Pamela L., 1968- (Book collections on Project MUSE., 1997)
Linked by their focus on the sport and practice of body building, the authors in this volume challenge both the way their various disciplines (media studies, literary criticism, gender studies, film and sociology) have gone about studying bodies, and existing assumptions about the complex relationship between power, subjectivity, society, and flesh. Body building - in practice, in representation, and in the cultural imagination - serves as an launching point because the sport and practice provide ready challenges to existing assumptions about the "built" body.